The dynamics of tourism discourses and policy in Brazil. (March 2016) - Fazito, Mozart; Scott, Mark; Russell, Paula
Highlights: We studied policy-making for tourism development in Brazil. We identified and described five competing storylines of tourism development. We discussed their interactions in the local policy arenas and the policy outcomes. Sustainable tourism is described as vague, imprecise and fragile discourse. Foucauldian discourse analysis was crucial to reveal the discourse dynamics. Abstract: This article employs a Foucauldian inspired discourse analysis in order to unveil hidden aspects of the tourism development policy-making process in the UNESCO Espinhaço Range Biosphere Reserve, Brazil. It identifies the emergence of different representations of tourism development and demonstrates the process of social construction of sustainable tourism as an overarching discourse, which incorporates different—sometimes opposing—representations of tourism development to gather the support of people with different backgrounds and interests. However, this research demonstrates that this flexibility caused the sustainable tourism narrative to become a vague and imprecise discourse in the context of the case study, which has been used by the regional elites to conserve the status quo, but disguised as a critical alternative perspective.